Public policies for inclusive education in Brazil and Bahia: advances and returns (Research, Society and Development, 2021)
This article aims to analyze the trajectory of educational policies for special / inclusive education in Brazil, as well as to point out the perspectives of this type of teaching in the State of Bahia. For this, we adopted bibliographic and documentary research as methodological procedures. Regarding the bibliographic review, we used the studies of Jannuzzi & Caiado (2013), Mazzota (1996), Mantoan (2002), Cruz & Monteiro (2019), Oliveira & Glat (2003), among others; Among the documentary sources, we use the Salamanca Declaration and some educational legislation, such as the National Education Guidelines and Bases Laws, No. 4024/1961 and No. 9394/1996 and, at the regional level, the Inclusive Education Guidelines for People with Disabilities, Global Development Disorders and High Skills / Giftedness (2017), a document prepared by the State of Bahia. By observing the aspects analyzed, we highlight the need for joint action by all segments of society in order to minimize the distance between legal provisions and school life.